Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

How can I find the following limit:

$$\lim_{x\rightarrow \infty}\frac{\ln(1+\alpha x)}{\ln(\ln(1+\text{e}^{\beta x}))}$$

where $\alpha, \ \beta \in \mathbb{R}^+$.

My first guess was to use l'Hospital:

$$\lim_{x\rightarrow \infty}\frac{\ln(1+\alpha x)}{\ln(\ln(1+\text{e}^{\beta x}))} = \lim_{x\rightarrow \infty}\frac{\ln(1+\text{e}^{\beta x})(1+\text{e}^{\beta x}) \ \alpha}{(1 + \alpha x) \ \text{e}^{\beta x} \ \beta}$$

But what can I do now? Is my approach correct or is there a simpler method?

Edit: Taking the advice from Daniel Fischer, $$\lim_{x\rightarrow \infty}\frac{\ln(1+\text{e}^{\beta x})(1+\text{e}^{\beta x}) \ \alpha}{(1 + \alpha x) \ \text{e}^{\beta x} \ \beta} = \lim_{x\rightarrow \infty}\frac{\ln(1+\text{e}^{\beta x}) \ \alpha}{(1 + \alpha x) \ \beta} \lim_{x\rightarrow \infty}(1+\text{e}^{-\beta x}) $$

Applying L'Hospital a second time on the first fraction,

$$\lim_{x\rightarrow \infty}\frac{\ln(1+\text{e}^{\beta x}) \ \alpha}{(1 + \alpha x) \ \beta} \lim_{x\rightarrow \infty}(1+\text{e}^{-\beta x}) = \lim_{x\rightarrow \infty}\frac{\alpha \ \beta \ \text{e}^{\beta x}}{(1+\text{e}^{\beta x}) \ \alpha \ \beta} \cdot 1 = \lim_{x\rightarrow \infty}\frac{\text{e}^{\beta x}}{1+\text{e}^{\beta x} } \cdot 1 $$

Now let's apply L'Hospital one final time: $$\lim_{x\rightarrow \infty}\frac{\text{e}^{\beta x}}{1+\text{e}^{\beta x} } \cdot 1 = \lim_{x\rightarrow \infty}\frac{\text{e}^{\beta x}\ \beta}{\text{e}^{\beta x}\ \beta} \cdot 1 = 1$$

Is this correct?

share|cite|improve this question
You obtain $\frac{\infty}{\infty}$ after L'Hopital the first time so it doesn't hurt to try L'Hopital again and see where that leads. (Also, I think it should be $(1+\alpha x)e^{\beta x} \beta$ in the denominator which is obtained by LH.) – Gamma Function Jun 10 '14 at 11:53
You should have $1+ \alpha x$ in the denominator, not $1+\alpha$. Write $\frac{1+e^{\beta x}}{e^{\beta x}} = 1 + e^{-\beta x}$. Since that tends to $1$ as $x\to\infty$, you can remove that to simplify. – Daniel Fischer Jun 10 '14 at 11:54
Thanks for your comments! I edited my question. Can you verify if it's correct or did I make a mistake somewhere? – IronMan12 Jun 10 '14 at 13:20
up vote 1 down vote accepted

The first application of l'Hôpital's theorem gives $$ \lim_{x\to\infty} \frac{\alpha}{1+\alpha x} \left(\frac{\beta e^{\beta x}\big/(1+e^{\beta x})}{\log(1+e^{\beta x})}\right)^{-1} = \lim_{x\to\infty} \frac{\alpha}{\beta} \frac{1+e^{\beta x}}{e^{\beta x}} \frac{\log(1+e^{\beta x})}{1+\alpha x} $$ Now, $$ \lim_{x\to\infty}\frac{1+e^{\beta x}}{e^{\beta x}}= \lim_{x\to\infty}(e^{-\beta x}+1)=1 $$ so we just need to compute $$ \lim_{x\to\infty}\frac{\log(1+e^{\beta x})}{1+\alpha x}= \lim_{x\to\infty}\frac{\beta e^{\beta x}/(1+e^{\beta x})}{\alpha}= \lim_{x\to\infty}\frac{\beta}{\alpha}\frac{e^{\beta x}}{1+e^{\beta x}}= \frac{\beta}{\alpha} $$ You don't need anything new for this limit, because you have just computed the reciprocal.

share|cite|improve this answer
How come that your final result is $\beta / \alpha$ while Paramanand Singh has $1$ as final result? Where did the factor $\alpha/ \beta$ from the first equation go to? I'm a bit confused now. – IronMan12 Jun 11 '14 at 20:07
@IronMan12 I just studied separately the three factors in the final limit of the first display. The first factor is $\alpha/\beta$, the second has limit $1$, the third has limit $\beta/\alpha$. So the product is $1$. – egreg Jun 11 '14 at 20:09
Ah, wonderful. That makes sense. Thank you so much for your fast answer! – IronMan12 Jun 11 '14 at 20:11

without L'Hospital, but with Maclaurin series:

1) rewrite the numerator as $\log (\alpha x) + \log (1+ \frac{1}{\alpha x}) \sim \log \alpha + \log x + \frac{1}{\alpha x}$

2) rewrite the numerator as $\log (\log e^{\beta x} + \log (1+ \frac{1}{\beta x})) = \log (\beta x + \frac{1}{\beta x}) = \log \beta x(1+\frac{1}{(\beta x)^2}) \sim \log \beta +\log x + \frac{1}{(\beta x )^2}$

Can you handle from here?

share|cite|improve this answer

We can proceed as follows $$\begin{aligned}L &= \lim_{x \to \infty}\frac{\log(1 + \alpha x)}{\log(\log(1 + e^{\beta x}))}\\ &= \lim_{x \to \infty}\dfrac{\log\left(\dfrac{1 + \alpha x}{\alpha x}\right) + \log \alpha x}{\log\left(\log\left(\dfrac{1 + e^{\beta x}}{e^{\beta x}}\right) + \beta x\right)}\\ &= \lim_{x \to \infty}\frac{y + \log \alpha x}{\log(z + \beta x)} \text{ where }y = \log((1 + \alpha x)/\alpha x), z = \log((1 + e^{\beta x})/e^{\beta x})\\ &= \lim_{x \to \infty}\frac{y + \log \alpha x}{\log(z + \beta x) - \log \beta x + \log \beta x}\\ &= \lim_{x \to \infty}\frac{y + \log \alpha x}{\dfrac{z}{c} + \log \beta x}\text{ where }c \in (\beta x, \beta x + z)\text { by Mean Value Theorem}\\ &= \lim_{x \to \infty}\frac{y + \log \alpha x}{t + \log \beta x}\text{ where }t = z/c\\ &= \lim_{x \to \infty}\frac{y + \log \alpha + \log x}{t + \log \beta + \log x}\\ &= \lim_{x \to \infty}\dfrac{\dfrac{y}{\log x} + \dfrac{\log \alpha}{\log x} + 1}{\dfrac{t}{\log x} + \dfrac{\log \beta}{\log x} + 1}\\ &= \frac{0 + 0 + 1}{0 + 0 + 1} = 1\end{aligned}$$ Here we have used the fact that $\alpha > 0, \beta > 0, y > 0, z > 0$ and as $x \to \infty$ we have $y \to 0$, $z \to 0$, $c \to \infty$ and $t \to 0$.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.